Participatory Action Research Strategy: The Role of Culture in the Transformation of Religious Development - Liwun, Karolus Lawe; Rachmawati, Tutik (Department of Public Administration, Parahyangan Catholic University, 2024)
This paper aims to explain the effective cultural approach strategies in the development of the Catholic religion in St. Herman Yoseph Riangkemie, Larantuka Diocese. The approach begins with studying the cultural values of the local community and integrating them with Catholic religious values to be applied in the community's life, with the goal of changing the local community's perception of the religion. The research method used in this study is qualitative with a participatory action research approach. The results of religious development using this cultural approach have shown success in increasing the community's awareness to engage in religious activities and enhancing their sense of responsibility in religious development. This approach has significantly helped increase the number of Catholic Church members in the area.